Evaluation of Pre-Marriage Counseling Program in Iran: A Narrative Review of Structural, Procedural, and Outcome Dimensions - Mohammad Hossein Mehrolhassani; Vahid Yazdi-Feyzabadi; Afsaneh Rajizadeh (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Pre-marriage counseling program, an educational intervention launched in 1993, makes the married couples familiar to maternal health issues. In order to improve the performance of this program, it is necessary to examine the various dimensions of this program. Therefore, the present study was designed and implemented to evaluate the pre-marriage counseling program. Methods: In this narrative review study, the use of standard key words, articles indexed in the databases of PubMed, Web of Science, Scopus, SID, BarakatKNS (IranMedex) and Magiran by the end of April 2017 were reviewed. Finally, the full text of 56 articles was examined, and the content of these articles was classified according to the quality assessment framework of Donabedian in three dimensions, including structure, process, and outcome of this program. Results:   After categorizing the results of the articles based on the Donabedian's framework, 21, 8 and 41 articles were related and classified in structure, process and outcome, respectively. Most of the studies conducted between 2001 and 2011 were mostly cross-sectional, and the highest number of articles was in the outcome dimension. Structural dimension was subdivided into four sub-categories including educational content, human resources, facilities, and information resources. Then the process was sub-divided into training and counseling mechanism and eventually the outcome. Conclusion:   In the dimension of the structure, the assessment of the educational materials' contents was poor.  In the dimension of the process, the duration of training should be increased.  In the outcome dimension, the level of participants' knowledge and attitude about sexual health, reproductive health and sexually transmitted diseases was assessed moderate to weak.